Artikel review : validasi metode penentuan kadar asam retinoat pada sediaan kosmetik dalam bentuk krim dengan menggunakan berbagai instrumen - Tanjaya, Steve Pratama; Rosyada, Sabila; Octavia, Ditha Zanetti; Putri, Dewi Angelita; Nadiya, Aisya; Pratiwi, Eskarani Tri (Sasambo Journal of Pharmacy, 2025)
Whitening cream cosmetics are widely used to treat skin and are often employed to lighten the complexion of skin and reduce marking. Unfortunately, these products mostly contain hazardous ingredients like retinoic acid, effective yet capable of causing harm with its side effects in terms of skin inflammation, desiccation, and teratogenicity. This review will discuss the evaluation and comparison of the validity of the analytic method in the determination of retinoic acid in cosmetic cream formulations with different instruments; High-Performance Liquid Chromatography, Chromatography-Photodiode Array Detector, and UV-Vis Spectrophotometry methods were discussed. The conducted review used a literature review method wherein various national and international relevant studies of these analytic techniques had been analyzed. Results indicate that HPLC, especially with UV detection, presents the highest accuracy, precision, and sensitivity for quantifying retinoic acid, although it requires a longer analysis time. UV-Vis Spectrophotometry, on the other hand, though less sensitive, offers advantages in terms of simplicity, cost, and shorter duration of the analysis. Among the methods reviewed here, HPLC provides comprehensive validation parameters, demonstrating a linearity of 0.9999, an RSD of 0.99%, an accuracy of 114.3%, an LOD of 0.0165 ppm, and an LOQ of 0.0495 ppm.. Therefore, in order to ensure the safety and regulatory compliance of cosmetic products, the validation of the analytical methodologies for the detection of retinoic acid becomes indispensable, and hence the selection of the most optimal technique is highly relevant.